2022
DOI: 10.1590/0037-8682-0671-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of El Niño Southern Oscillation on the dengue transmission dynamics in the Metropolitan Region of Recife, Brazil

Abstract: Developing of the manuscript, production of the results and graphics and interpretation of data; RSN: constructions of the ideas, elaboration of manuscript and support in the analysis of the relationships between climatic variables and dengue incidence; PSB: contribution in the interpretation and showing of the structure of methodology; JPF: contributions to analyze epidemiological characteristics and constructions of the ideas; JHA: contributions to analyze, review and constructions of the ideas; EBM: contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…During 2015 and at the beginning of 2019 there were warm periods related to oceanatmosphere temperature [47]. These results are in line with previous studies that found evidence that ENSO is associated with dengue outbreaks [48,49]. Considering the number of dengue cases that occurred in 2015 and 2019, the ENSO phenomenon is an important factor to be considered in any early warning system.…”
Section: Discussionsupporting
confidence: 88%
“…During 2015 and at the beginning of 2019 there were warm periods related to oceanatmosphere temperature [47]. These results are in line with previous studies that found evidence that ENSO is associated with dengue outbreaks [48,49]. Considering the number of dengue cases that occurred in 2015 and 2019, the ENSO phenomenon is an important factor to be considered in any early warning system.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, intense El Niño conditions and associated droughts seem to be an early indicator that appropriate conditions exist for epidemic transmission of arboviruses the following year in Puerto Rico. Ferreira et al (2022) issued recommendations to intensify vector and other arbovirus control mechanisms as early as El Niño is detected in northeastern Brazil. Several studies have shown that warm El Niño conditions precede dengue epidemics by several months (Anyamba et al 2019; Kovats et al 2003, Tipayamongkholgul et al 2009,Colón-González et al 2013; Vicenti-Gonzalez et al 2018).…”
Section: Discussionmentioning
confidence: 99%